Clinical profile and seroepidemiology of scrub typhus and its concurrent infections associated with other tropical fevers: a two-year study from a tertiary care centre in North India - Matlani, Monika; Maheshwari, Supriya; Dubey, Neha; Mina, Shyam S.; Dogra, Vinita (International Journal Of Community Medicine And Public Health, 2020)
Background: The study showed epidemiological aspects, clinical profile and laboratory features of patients presenting with scrub typhus alone and scrub typhus along with concurrent infections namely typhoid, malaria, leptospira, chikungunya and dengue. Methods: A total of 383 suspected cases of Scrub typhus were tested by IgM ELISA from January 2017 to October 2018. Appropriates tests were performed to determine the coinfections of scrub typhus with dengue, chikungunya, malaria, leptospirosis and typhoid fever. Results: Of the 383 samples received, 68 were positive for scrub typhus. Commonest clinical manifestations were fever, shortness of breath, myalgia, headache and jaundice. Maximum number of co infection cases were observed along with dengue. Conclusions: With the rapidly changing epidemiology of scrub typhus, it is very important to become familiar with its clinical presentation when presenting alone and as a concurrent infection with other acute febrile infections.